The Nanofabrication and Application of Substrates for Surface-Enhanced Raman Scattering. (19th December 2012) - Zhang, Xian; Zhou, Qin; Huang, Yu; Li, Zhengcao; Zhang, Zhengjun
Abstract : Surface-enhanced Raman scattering (SERS) was discovered in 1974 and impacted Raman spectroscopy and surface science. Although SERS has not been developed to be an applicable detection tool so far, nanotechnology has promoted its development in recent decades. The traditional SERS substrates, such as silver electrode, metal island film, and silver colloid, cannot be applied because of their enhancement factor or stability, but newly developed substrates, such as electrochemical deposition surface, Ag porous film, and surface-confined colloids, have better sensitivity and stability. Surface enhanced Raman scattering is applied in other fields such as detection of chemical pollutant, biomolecules, DNA, bacteria, and so forth. In this paper, the development of nanofabrication and application of surface-enhanced Ramans scattering substrate are discussed.